Molecular Mechanisms of Recurrent Pregnancy Loss - Bahareh Mazrouei, Mohammad Mehdi Heidari; Mehri Khatami; Maryam Tahmasebi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2020)
Introduction: Pregnancy and health is the process in which the egg is fertilized and being able to survive. When pregnancy occurs under some conditions and the fetus is being at risk, it will lead to abortion that occurs involuntarily and spontaneously. Abortions that occur more than two or three times are called recurrent pregnancy loss (RPL). Various etiological factors involved in RPL, including environmental, pathological and genetic factors. The environmental factors that often related to an inappropriate lifestyle, and endanger the pregnancy. The pathological factors are including autoimmune, infectious, endocrine and anatomical factors. The genetic factors are including several structural and chromosomal abnormalities. The majority of chromosomal abnormalities are including trisomy, polyploidy, and monosomy X. The structural abnormalities due to chromosomal cleavage, which may be balanced or unbalanced. However, a large number of these abortions do not have any clear reason, so molecular studies have shown that these types of recurrent pregnancy losses are related to the gene disorders of the mother. The function of these genes shows that they are associated with the process of formation, implantation and maintenance, fetal growth and development, and so on. This review focuses on the genetic and molecular abnormalities that may involve in the occurrence of recurrent pregnancy loss to choose the appropriate treatment for couples who suffer from RPL, based on the type of disorder.